(untitled) (Journal of Partial Differential Equations, 2003)
" In this paper, we derive the local estimates of a singular solution near its singular set Z of the Gaussian curvature equation 0394u(x) + K(x)e^u(x) = 0 in 03a9 Z, in the case that K(x) may be zero on Z, where 03a9 2282 R00b2 is a bounded open domain, and Z is a set of finite points."